2022
DOI: 10.19184/ejeba.v9i1.30412
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Pasar Modal Syariah 5 Negara Asean di Era Pandemi COVID 19

Abstract: One of the efforts made to measure the stability of the economy in a country is by looking at the performance of its stock market. The stock market can be said to have a good performance, if it is able to reflect prices that are relevant to the news that is developing in the community. The purpose of this study was to examine the influence of the Islamic capital market in 5 ASEAN countries in the era of the Covid-19. This study uses a quantitative approach with daily data in 2020 as the database. The analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…The Covid-19 pandemic created a pessimistic among investors toward the company's future [26], causing investors immediately selling their shares. The pessimistic attitude of investors can be seen from the panic of investors in responding to any information about COVID-19 that causes price fluctuations and stock trading [31]. Therefore, the first hypothesis in the study is: H1a: negative investor sentiment affects stock returns H1b: positive investor sentiment affects stock returns.…”
Section: The Effect Of Investor Sentiment On Stock Returns During The...mentioning
confidence: 99%
“…The Covid-19 pandemic created a pessimistic among investors toward the company's future [26], causing investors immediately selling their shares. The pessimistic attitude of investors can be seen from the panic of investors in responding to any information about COVID-19 that causes price fluctuations and stock trading [31]. Therefore, the first hypothesis in the study is: H1a: negative investor sentiment affects stock returns H1b: positive investor sentiment affects stock returns.…”
Section: The Effect Of Investor Sentiment On Stock Returns During The...mentioning
confidence: 99%
“…Tetteh et al (2022) report that the case reports including the death rate from Covid-19 had a negative impact on the performance of financial markets in Ghana and Botswana from March 1, 2020, to September 30, 2021. At the ASEAN level, some studies from Dewi et al (2021), Octavera and Rahadi (2021), and Romadhon and Ardiansyah (2022) report that capital market conditions have worsened due to the Covid-19 pandemic. Some studies as found by Putri (2020), Nasution et al (2020), Sumarni (2020), Aeni (2021), Hamzah et al (2021), and Akhmad (2022) also report the adverse impact of Covid-19 on the economy and especially the capital market in Indonesia.…”
Section: Introductionmentioning
confidence: 99%
“…There are various ways to measure the level of economic stability in a country and one of them is by measuring the performance of its stock market. Performance in the stock market can be said to be good if it can reflect prices that are relevant to the news that develops in the community (Romadhon & Ardiansyah, 2022).…”
Section: Introductionmentioning
confidence: 99%